Intelectual Capital, Tipe Kepemilikan dan Nilai Perusahaan - Surifah Surifah; Arina Hidayati; Suyanto Suyanto (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
The purpose of this research is to provide empirical evidence of the effect of intellectual capital and ownership type on firm value. This research was conducted on consumer goods industry companies listed on the Indonesia Stock Exchange in 2017-2021. Samples were selected purposefully with certain criteria. The final sample of 190 observations The dependent variables are Tobin's Q and Price to Book Value. Independent variables consist of human capital, structural capital, customer capital, domestic ownership, foreign ownership, government ownership, and individual ownership. The control variable is leverage. Analysis was performed using panel data linear regression and processed with statistical software. The results show that customer capital and foreign ownership have a positive effect on firm value, both measured by PBV and Tobin's Q. Domestic ownership has a positive effect on Tobin's Q but has no effect on PBV. Leverage has a negative effect on PBV, but has no effect on Tobin's Q. Variable human capital, capital structure, government ownership, and individual ownership have no effect on firm value.